(untitled) (Modern education and development, 2025)
This article explores the expression of national spirit in the short stories of Abdulhamid Cho‘lpon, one of the leading figures of Uzbek literature in the early 20th century. Focusing on two of his notable stories — “On Bright Nights” (Oydin kechalarda) and “A Tulip in the Snow” (Qor qo‘ynida lola) — the article analyzes how Cho‘lpon embeds traditional values, spiritual identity, and social critique within the framework of poetic realism. The stories reflect not only the cultural and emotional realities of Uzbek people during a period of sociopolitical turmoil but also assert the importance of national identity in literature.